Targeting CXCL1 chemokine signaling for treating cisplatin ototoxicity - Al Aameri, Raheem F. H.; Alanisi, Entkhab M. A.; Oluwatosin, Adu; Al Sallami, Dheyaa; Sheth, Sandeep; Alberts, Ian; Patel, Shree; Rybak, Leonard P.; Ramkumar, Vickram (Frontiers in Immunology, 2023)
Cisplatin is chemotherapy used for solid tumor treatment like lung, bladder, head and neck, ovarian and testicular cancers. However, cisplatin-induced ototoxicity limits the utility of this agent in cancer patients, especially when dose escalations are needed. Ototoxicity is associated with cochlear cell death through DNA damage, the generation of reactive oxygen species (ROS) and the consequent activation of caspase, glutamate excitotoxicity, inflammation, apoptosis and/or necrosis. Previous studies have demonstrated a role of CXC chemokines in cisplatin ototoxicity. In this study, we investigated the role of CXCL1, a cytokine which increased in the serum and cochlea of following cisplatin administration. Adult male Wistar rats treated with cisplatin demonstrate significant hearing loss, assessed by auditory brainstem responses (ABRs), hair cell loss and loss of ribbon synapse loss. Immunohistochemical studies evaluated the levels of CXCL1 along with increased presence of CD68 and CD45-positive immune cells in cochlea. Increases in CXCL1 was time-dependent and was associated with a progressive increase in CD45, CD68 and IBA1-positive immune cells predominantly in the stria vascularis, spiral ligament and spiral ganglion neurons. Similarly, knockdown of CXCR2 by trans-tympanic administration of CXCR2 siRNA protected against hearing loss and loss of outer hair cells and reduced ribbon synapses. Trans-tympanic administration of SB225002, a chemical inhibitor of CXCR2 (receptor target for CXCL1) reduced immune cell migration, protected against cisplatin-induced hearing loss and preserved hair cell integrity. We show that SB225002 reduced the expression of CXCL1, NOX3, iNOS, TNF-α, IL-6 and COX-2. These results implicate the CXCL1 chemokine as an early player in cisplatin ototoxicity, possibly by initiating the immune cascade, and indicate that CXCR2 is a relevant target for treating cisplatin ototoxicity.